The body project 4 all: A pilot randomized controlled trial of a mixed‐gender dissonance‐based body image program. Issue 6 (18th May 2016) - Kilpela, Lisa Smith; Blomquist, Kerstin; Verzijl, Christina; Wilfred, Salomé; Beyl, Robbie; Becker, Carolyn Black
ABSTRACT: Objective: The Body Project is a cognitive dissonance‐based body image improvement program with ample research support among female samples. More recently, researchers have highlighted the extent of male body dissatisfaction and disordered eating behaviors; however, boys/men have not been included in the majority of body image improvement programs. This study aims to explore the efficacy of a mixed‐gender Body Project compared with the historically female‐only body image intervention program. Method: Participants included male and female college students ( N = 185) across two sites. We randomly assigned women to a mixed‐gender modification of the two‐session, peer‐led Body Project (MG), the two‐session, peer‐led, female‐only (FO) Body Project, or a waitlist control (WL), and men to either MG or WL. Participants completed self‐report measures assessing negative affect, appearance‐ideal internalization, body satisfaction, and eating disorder pathology at baseline, post‐test, and at 2‐ and 6‐month follow‐up. Results: Linear mixed effects modeling to estimate the change from baseline over time for each dependent variable across conditions were used. For women, results were mixed regarding post‐intervention improvement compared with WL, and were largely non‐significant compared with WL at 6‐month follow‐up. Alternatively, results indicated that men in MG consistently improved compared with WL through 6‐month follow‐up on all measures except negative affect and appearance‐ideal internalization. Discussion: Results differed markedly between female and male samples, and were more promising for men than for women. Various explanations are provided, and further research is warranted prior to drawing firm conclusions regarding mixed‐gender programming of the Body Project . © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2016; 49:591–602)